Fibroblast activation in response to TGFβ1 is modulated by co-culture with endothelial cells in a vascular organ-on-chip platform - Luu, Rebeccah J.; Hoefler, B. Christopher; Gard, Ashley L.; Ritenour, Casey R.; Rogers, Miles T.; Kim, Ernest S.; Coppeta, Jonathan R.; Cain, Brian P.; Isenberg, Brett C.; Azizgolshani, Hesham; Fajardo-Ramirez, Oscar R.; García-Cardeña, Guillermo; et al. (Frontiers in Molecular Biosciences, 2023)
Tissue fibrosis is a major healthcare burden that affects various organs in the body for which no effective treatments exist. An underlying, emerging theme across organs and tissue types at early stages of fibrosis is the activation of pericytes and/or fibroblasts in the perivascular space. In hepatic tissue, it is well known that liver sinusoidal endothelial cells (EC) help maintain the quiescence of stellate cells, but whether this phenomenon holds true for other endothelial and perivascular cell types is not well studied. The goal of this work was to develop an organ-on-chip microvascular model to study the effect of EC co-culture on the activation of perivascular cells perturbed by the pro-fibrotic factor TGFβ1. A high-throughput microfluidic platform, PREDICT96, that was capable of imparting physiologically relevant fluid shear stress on the cultured endothelium was utilized. We first studied the activation response of several perivascular cell types and selected a cell source, human dermal fibroblasts, that exhibited medium-level activation in response to TGFβ1. We also demonstrated that the PREDICT96 high flow pump triggered changes in select shear-responsive factors in human EC. We then found that the activation response of fibroblasts was significantly blunted in co-culture with EC compared to fibroblast mono-cultures. Subsequent studies with conditioned media demonstrated that EC-secreted factors play at least a partial role in suppressing the activation response. A Luminex panel and single cell RNA-sequencing study provided additional insight into potential EC-derived factors that could influence fibroblast activation. Overall, our findings showed that EC can reduce myofibroblast activation of perivascular cells in response to TGFβ1. Further exploration of EC-derived factors as potential therapeutic targets in fibrosis is warranted.